2021
DOI: 10.1532/hsf.3415
|View full text |Cite
|
Sign up to set email alerts
|

Can Peroperative Neutrophil To Lymphocyte Ratio Change (Deltanlr) Be Used as a Parameter in Predicting Acute Renal Failure Following Coronary Bypass Operations With Cardiopulmonary Bypass?

Abstract: Background: Inflammation plays a significant role in the pathogenesis of many diseases as well as postoperative acute renal failure (ARF). Preoperative neutrophil to lymphocyte ratio (NLR) values have a prognostic value for postoperative ARF after cardiovascular surgeries. Methods: Patients who underwent elective coronary artery bypass graft (CABG) with cardiopulmonary bypass in our clinic between December 15, 2015 and December 15, 2019, retrospectively were included in this study. Patients who did not develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our results showed that preoperative serum creatinine was significantly higher in patients in the AKI group compared with those in non-AKI group and was positively correlated with the highest blood creatinine value, suggesting that the earlier the onset and the greater the elevation of blood creatinine, the greater the likelihood of AKI. After adjusting other risk factors, high preoperative serum creatinine levels also significantly increased the risk of postoperative AKI, which was consistent with previous studies [8,19,20]. Previous studies showed that preoperative serum creatinine ≥ 1.3 mg/dl was an independent risk factor for AKI associated with cardiac surgery, which was largely similar to our results [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that preoperative serum creatinine was significantly higher in patients in the AKI group compared with those in non-AKI group and was positively correlated with the highest blood creatinine value, suggesting that the earlier the onset and the greater the elevation of blood creatinine, the greater the likelihood of AKI. After adjusting other risk factors, high preoperative serum creatinine levels also significantly increased the risk of postoperative AKI, which was consistent with previous studies [8,19,20]. Previous studies showed that preoperative serum creatinine ≥ 1.3 mg/dl was an independent risk factor for AKI associated with cardiac surgery, which was largely similar to our results [21].…”
Section: Discussionsupporting
confidence: 93%
“…Studies showed that NLR had the positive correlation and synchronous changes with various classical inflammatory indices, indicating the state of renal function during the inflammation and disease processes [ 7 ]. However, existing studies have shown the conflicting predictive value of preoperative NLR for postoperative AKI in patients undergoing CABG alone [ 6 , 8 ]. In this study, we aimed to investigate the correlation between preoperative NLR and postoperative AKI after ONCAB, and the combined predictive value of preoperative NLR with other indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Today, coronary artery bypass graft (CABG) operations are widely performed, and the success of the procedure is influenced by complications that develop after the operation besides surgical technique [Erdolu 2020]. One of the most important complications is acute kidney injury (AKI) clinic, which can occur after the operations [Usta 2021]. In addition, 20-30% of diabetes mellitus (DM) is detected in patients with CABG planned.…”
Section: Introductionmentioning
confidence: 99%
“…From 10 studies 41–50 involving 7660 patients, we found a statistically significant association between elevated preoperative NLR and postoperative AKI (OR 1.45, 95% CI 1.18–1.77) (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
“…From six studies [42][43][44][45]47,48 with 3637 patients, we found no association between elevated NLR at postoperative day 1 (POD1) and postoperative AKI (OR 1.43, 95% CI 0.94-2.16) (Figure 4). Similarly, meta-regression could not be performed to assess the substantial heterogeneity (I 2 statistic 99.9%) due to insufficient study numbers.…”
Section: Postoperative Day 1 Nlr Measurementmentioning
confidence: 95%